Osmos-Life-Consciousness V (Global Journal of Science Frontier Research, 2023)
In the Introduction comments are made on the topic and on the difficulties arising from being the same multidisciplinary subject with each discipline being the subject of a large volume of research and publications In Discussion and Conclusions he addresses the subject in three topics believing this to be the most convenient way to describe the arguments presented as indications In the first topic Time and Space considerations are made involving the speed of light The possibility is highlighted that phenomena occurring outside the cone of light may cause effects that are different from the usual ones making them apparently inexplicable to us The thinkers Plat o Einstein Kant and Penrose are cited briefly presenting their ideas on the matter Regarding the topics The beginning of everything and Platonic world-Consciousness- Mind it shows below the ideas or hypotheses formulated leaving to the reader the task of analyzing the indications presented in the text that led him to formulate them
Keywords: cosmos; life; consciousness; mind